In the midst of the coronavirus and geopolitical crises: Inventory efficiency and challenges faced in Finland - Olli-Pekka Hilmola (Journal of Risk and Financial Management, 2023)
Before the COVID-19 pandemic, the world lived through loose monetary policy and low interest rates. These were further reinforced in 2020, and product-based demand increased throughout the world. Due to these, as well as the suddenly developing geopolitical crisis in Ukraine, inflation started to accelerate (both consumer and producer), and this was especially the case in Europe. Therefore, there is a need for descriptive analysis on how trade and manufacturing companies have reacted to the existing multifaced crisis. This research used data of Finnish publicly traded companies. On the basis of the results, inventories increased in the longer term, especially in 2021 and 2022 (the first half of the year). Content analysis revealed reasons for inventory build-up in 2021-2022, with these being the result of many different causes. In some cases, business expansion or decline was said to be the reason, while in others, it was availability issues faced and purchasing price increases experienced. Interestingly, Russia was directly mentioned as a reason by only a few companies.
Keywords: 650; COVID-19; Finland; inventory efficiency; geopolitics